2014
DOI: 10.1103/physrevx.4.031045
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of Skyrmions in Two-Dimensional Chiral Magnets with Rashba Spin-Orbit Coupling

Abstract: Recent developments have led to an explosion of activity on skyrmions in three-dimensional (3D) chiral magnets. Experiments have directly probed these topological spin textures, revealed their non-trivial properties, and led to suggestions for novel applications. However, in 3D the skyrmion crystal phase is observed only in a narrow region of the temperature-field phase diagram. We show here, using a general analysis based on symmetry, that skyrmions are much more readily stabilized in two-dimensional (2D) sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
205
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(229 citation statements)
references
References 54 publications
21
205
2
1
Order By: Relevance
“…1. Previous theoretical studies have focused on the skyrmion phase diagram of infinite systems at zero temperature [8,26] and nonzero temperature in two and three dimensions [27,28]. The first experimental results on bulk materials [9][10][11] have been extended to confined geometries, such as thin films, e.g., of MnSi [29] and FeGe [30].…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…1. Previous theoretical studies have focused on the skyrmion phase diagram of infinite systems at zero temperature [8,26] and nonzero temperature in two and three dimensions [27,28]. The first experimental results on bulk materials [9][10][11] have been extended to confined geometries, such as thin films, e.g., of MnSi [29] and FeGe [30].…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…7,8 Similarly, skyrmions are of interest from a fundamental perspective and for their ability to potentially enable low-power spintronics, and these spin states are stabilized by a reduction from three to two dimensions and by the presence of Rashba spin-orbit coupling. 9,10 In general, spin-orbit coupling within heterostructures should yield interesting spin structures and magnetoelectric transport.…”
Section: Introductionmentioning
confidence: 99%
“…Since this initial discovery there has been tremendous growth in the field as an increasing number of materials have been found that can support a skyrmion phase [3][4][5][6][7][8][9][10] . There are also numerous proposals on how to stabilize skyrmion states by utilizing different materials properties or bilayers [11][12][13][14] . Direct imaging of skyrmions with Lorentz microscopy [3][4][5]7,10 and other techniques 8,15,16 show that the skyrmions form a triangular lattice and have particle-like properties similar to vortices in type-II superconductors 17 .…”
Section: Introductionmentioning
confidence: 99%